In vitro Differentiation of Murine Innate Lymphoid Cells from Common Lymphoid Progenitor Cells - Seehus, Corey (Bio Protoc, 2016)
Subtypes of innate lymphoid cells (ILC), defined based on their cytokine secretion profiles and transcription factor expression, are important for host protection from pathogens and maintaining tissue homeostasis. ILCs develop from common lymphoid progenitors (CLP) in the bone marrow. Using the methods described here, we have previously shown that loss of the transcriptional regulator TOX (Thymocyte-selection associated HMG-box protein) leads to specific changes in ILC development and differentiation. Here, we describe how to obtain ILCs from in vivo isolated CLP grown in vitro.